Antonym in Surah Al-Furqan (Analysis of Ali Al-khulli's Semantics of Meaning Relations) - Mufid, Miftahul; Diantika, Devi Eka (Universitas Yudharta Pasuruan, 2023)
In semantics, there are seven relations of meaning. One of them is an antonym. In this research, the researcher specializes in antonym verses in Surah Al-Furqan. In this surah, there are many antonym verses. The purpose of this research is first to understand sentences that show antonyms. Second, understand the various antonyms in surah Al-Furqan. This research method uses a qualitative-descriptive approach. They are used in analyzing semantics according to Ali Al-Khulli about the relationship of antonyms in surah Al-Furqan. The results of the research concluded, first: there are fourteen verses that show antonyms in surah Al-Furqan. Second: there are five types of antonyms in surah Al-Furqan. This research provides a new understanding of semantic theory in the context of the Qur'an, particularly concerning the theory of antonyms in identifying the meaning of antonyms in the language used by the Qur'an.